2009 IEEE/RSJ International Conference on Intelligent Robots and Systems 2009
DOI: 10.1109/iros.2009.5354220
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the terrestrial locomotion of a salamander robot

Abstract: Salamanders propel themselves by proper coordination of limb movements and body undulations. This type of locomotion is interesting for robotics to design robots capable of locomotion on water and land. In this work we identify the control and structural parameters that contribute to forward terrestrial locomotion. We introduce a kinematic model of Salamandra robotica II, a new salamander robot, to explore how the stride length varies with different limb sizes and different types of body oscillations. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…However, both the model and the robot showed that there is a maximum value of bending after which the stride length starts to decay (Fig. 3b in Karakasiliotis and Ijspeert 2009). To a large extent, this decelerating performance is a result of the "double crank" mechanism used for the limbs (i.e., feet positions are directly coupled to spinal kinematics).…”
Section: Terrestrial Steppingmentioning
confidence: 99%
See 4 more Smart Citations
“…However, both the model and the robot showed that there is a maximum value of bending after which the stride length starts to decay (Fig. 3b in Karakasiliotis and Ijspeert 2009). To a large extent, this decelerating performance is a result of the "double crank" mechanism used for the limbs (i.e., feet positions are directly coupled to spinal kinematics).…”
Section: Terrestrial Steppingmentioning
confidence: 99%
“…Lateral bending during forward walking Experiments with a kinematic model of Salamandra robotica II and the real robot showed that higher trunk bending yields greater stride length (Karakasiliotis and Ijspeert 2009;Crespi et al 2013. However, both the model and the robot showed that there is a maximum value of bending after which the stride length starts to decay (Fig.…”
Section: Terrestrial Steppingmentioning
confidence: 99%
See 3 more Smart Citations